2019
DOI: 10.5194/amt-2019-333
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of functional groups in atmospheric aerosols by infrared spectroscopy: method development for probabilistic modeling of organic carbon and organic matter concentrations

Abstract: Abstract. The Fourier transform infrared (FTIR) spectra of fine particulate matter (PM2.5) contain many important absorption bands relevant for characterizing organic matter (OM) and obtaining organic matter to organic carbon (OM/OC) ratios. However, extracting this information quantitatively – accounting for overlapping absorption bands and relating absorption to molar abundance – poses several challenges. For instance, a subset of model parameters lead to calibrations that test almost indistinguishably well … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 79 publications
(120 reference statements)
1
10
0
Order By: Relevance
“…In contrast, organic aerosols usually undergo several steps of oxidation and receive substantial condensation of oxidized vapors, which results in higher OM/OC ratio at rural and remote sites. Previous studies using several different methods (including FT-IR and AMS) show the same trend in urban and rural sites (Ruthenburg et al, 2014;Zhang et al, 2007;Simon et al, 2011;Bürki et al, 2019). In addition, the majority of the samples are in the range that is usually considered for OM/OC ratio, i.e.,1.4-1.7 (Russell, 2003).…”
Section: Om/oc Ratiomentioning
confidence: 58%
See 4 more Smart Citations
“…In contrast, organic aerosols usually undergo several steps of oxidation and receive substantial condensation of oxidized vapors, which results in higher OM/OC ratio at rural and remote sites. Previous studies using several different methods (including FT-IR and AMS) show the same trend in urban and rural sites (Ruthenburg et al, 2014;Zhang et al, 2007;Simon et al, 2011;Bürki et al, 2019). In addition, the majority of the samples are in the range that is usually considered for OM/OC ratio, i.e.,1.4-1.7 (Russell, 2003).…”
Section: Om/oc Ratiomentioning
confidence: 58%
“…This observation is consistent with the presence of molecules with longer chains, as observed for laboratory samples. Bürki et al (2019) showed that urban samples (in the same dataset) have their highest average OM/OC ratio in summer which is concurrent with the their highest A 1 /A 2 ratio which suggests shorter chain length. The highest A 1 /A 2 ratio for rural samples is observed in spring when the aerosols are highly oxidized (Bürki et al, 2019).…”
Section: Peak Height Ratios (mentioning
confidence: 77%
See 3 more Smart Citations